1999
DOI: 10.1103/physrevb.59.3696
|View full text |Cite
|
Sign up to set email alerts
|

Growth, structure, and magnetism of fcc Fe ultrathin films on Cu(111) by pulsed laser deposition

Abstract: Ultrathin Fe films on Cu͑111͒ have been grown by pulsed-laser deposition ͑PLD͒ whose instantaneous deposition rate is about six orders of magnitude larger than that of the conventional molecular-beam epitaxy based on thermal deposition ͑TD͒. Compared to the TD prepared Fe/Cu͑111͒ films, the PLD films have a significantly improved layer-by-layer morphology and a substantially enhanced stability of the fcc phase as characterized by scanning tunneling microscopy and electron-diffraction techniques. The magnetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 28 publications
4
46
0
Order By: Relevance
“…A question naturally arises: can we understand PLD in light of well-known MBE paradigm? There have been some theoretical 9,10 and experimental 11,12 studies comparing these two growth techniques in attempting to answer this question. The results of experimental studies are so sensitive to deposition conditions that it is crucial to compare the results from these two techniques under identical conditions 12 : same temperature calibration, background pressure, sample preparation, etc.…”
mentioning
confidence: 99%
“…A question naturally arises: can we understand PLD in light of well-known MBE paradigm? There have been some theoretical 9,10 and experimental 11,12 studies comparing these two growth techniques in attempting to answer this question. The results of experimental studies are so sensitive to deposition conditions that it is crucial to compare the results from these two techniques under identical conditions 12 : same temperature calibration, background pressure, sample preparation, etc.…”
mentioning
confidence: 99%
“…From the nucleation point of view, the interfacial energy and strain energy play an important role in the formation of nanoparticles in a supersaturated solid solution [10]. The lattice constants of fcc-Cu and fcc-Fe are 3.61 and 3.65 nm [25], respectively. The very small difference between their lattice constant leads to a very small strain energy and, hence, favors a coherent interface between the fcc Cu nanoparticles and austenite matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The energy-scanned photoelectron diffraction [7] measurements, however, reported an abrupt transformation with the entire film converting to bcc. In contrast, STM images [10] show bright needle like areas that are considered to be needle like domains of bcc Fe sitting on fcc Fe.…”
Section: Introductionmentioning
confidence: 89%
“…It is widely reported that Fe grows in a pseudomorphic fcc structure for the first few monolayer equivalents. Some LEED/AES investigations reported layer-by-layer growth [3,4], but angle-scanned photoelectron diffraction [5] and STM [10] measurements have shown that the Fe grows in 3-D islands and that the initial islands are mostly of bilayer height.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation